2021
DOI: 10.3390/antiox10121883
|View full text |Cite
|
Sign up to set email alerts
|

Pardaxin Activates Excessive Mitophagy and Mitochondria-Mediated Apoptosis in Human Ovarian Cancer by Inducing Reactive Oxygen Species

Abstract: Most ovarian cancer (OC) patients are diagnosed with stage III or higher disease, resulting in a poor prognosis. Currently, paclitaxel combined with carboplatin shows the best treatment outcome for OC. However, no effective drug is available for patients that do not respond to treatment; thus, new drugs for OC are needed. We evaluated the antimicrobial peptide, pardaxin, in PA-1 and SKOV3 cells. Pardaxin induced apoptosis as determined by MTT and TUNEL assays, as well as activation of caspases-9/3, Bid, t-Bid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Previous studies indicated that the PINK1/Parkin pathway was widely accepted as the chief mechanism of mitophagy, closely related to the regulation of mitochondrial membrane potential, mitochondrial fusion/fission and mitochondrial function [ 27 ]. Narendra et al demonstrated that Parkin is selectively recruited to dysfunctional mitochondria in mammalian cells and that after recruitment, Parkin mediates the engulfment of mitochondria by autophagosomes and their subsequent degradation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the PINK1/Parkin pathway was widely accepted as the chief mechanism of mitophagy, closely related to the regulation of mitochondrial membrane potential, mitochondrial fusion/fission and mitochondrial function [ 27 ]. Narendra et al demonstrated that Parkin is selectively recruited to dysfunctional mitochondria in mammalian cells and that after recruitment, Parkin mediates the engulfment of mitochondria by autophagosomes and their subsequent degradation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further study how autophagy induced by PM2.5 leads to apoptosis, we have further studied a special form of autophagy, mitophagy. Mitophagy is a cellular metabolic process, the role of which is to recover damaged mitochondria and maintain cell physiological functions [ 41 ], but continuous mitophagy may aggravate mitochondrial damage and induce cell apoptosis [ 42 , 43 ]. In this study, the fusion (yellow puncta) of mitochondria and autophagosomes is obviously observed in the cells treated with PM2.5, indicating that PM2.5 induces mitophagy in HaCaT cells ( Figure 8 (A)).…”
Section: Discussionmentioning
confidence: 99%
“…A number of cells (6 × 10 4 ) were then transferred to a 5 mL culture tube. All samples were processed for Annexin V label according to the literature [ 17 , 18 ]. At the end of the incubation, 1 mL of 1× binding buffer was added to each sample and the sample was analyzed using a flow cytometer Beckman Coulter cytometer (Beckman-Coulter, Brea, MI, USA) with the use of Cell Lab Quanta™ SC analysis software.…”
Section: Methodsmentioning
confidence: 99%
“…CellROX ® Green Reagent was applied to measure oxidative stress in live cells. The procedures for each staining method were conducted as described in the literature [ 17 ]. The fluorescence yielded from the staining reagents was detected using a Beckman Coulter cytometer (Beckman-Coulter, MI, USA) with the use of Cell Lab QuantaTM SC analysis software.…”
Section: Methodsmentioning
confidence: 99%